The invention of romance - Massing, Conni L. (Conni Louise), 1958- (Online access: Bloomsbury Publishing Drama Online: Playwrights Canada Press., 2017)
A rom-com with a twist, The Invention of Romance challenges notions of love as it explores the contrasting romantic fortunes of a young woman and her mother.